Liquidity risk and yield spreads of green bonds - Febi Wulandari; Dorothea Schäfer; Andreas Stephan; Chen Sun (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This study analyses how liquidity risk affects bonds' yield spreads after controlling for credit risk, bond-specific characteristics and macroeconomic variables. Using two liquidity estimates, LOT liquidity and the bid-ask spread, we find that, in particular, the LOT liquidity measure has explanatory power for the yield spread of green bonds. Overall, however, the impact of LOT decreases over time, implying that, nowadays liquidity risk is negligible for green bonds.
Keywords: G12; G32; 330; Green Bond; Liquidity Risk; Yield Spread; Sustainable Investment; Fixed Income Security; Financial Innovation